CRITICAL RESEARCH ON THE PEDAGOGICAL, INDIVIDUAL, AND SOCIAL IMPACT OF THE TOEFL PBT INTRODUCTION AS A TESTING INSTRUMENT - Imam Munandar (Englisia: Journal of Language, Education, and Humanities, 2019)
This research is a descriptive research by nature which tries to demonstrate various impacts to diverse communities. It gathers several important findings from previous research and draw a comprehensive outlook on how the TOEFL test has influenced the decision makers, teachers, students and outer community themselves. It is found that there has been a significant impact as the TOEFL test is administered as a test instrument worldwide. These include positive and negative impacts. For instance, the test has demanded schools to include teaching TOEFL preparation as an integrative part of syllabus. Still, students are forced to learn English intensively, but they are more inclined to attend the TOEFL class rather than regular classes. The research also shows that students prefer studying American English dialect since it is found in the test content. In wider community, the test opens job opportunities for many people especially publication industries and English private courses. However, the test also contributes to the inequality of educational opportunity between wealth and poor families.